Peningkatan keaktifan belajar dalam pembelajaran ips melalui penerapan model pembelajaran guided note taking pada peserta didik kelas iv sekolah dasar - Fauzia, Devya Alda; Marmoah, Sri; Suharno, Suharno (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
The objective of the reserach is to describe how to apply the Guided Note Taking (GNT) learning model that can improve learning activeness in social learning for fourth grade students of Ngadipuro Elementary School in Blora Regency. The type of research is Classroom Action Research conducted in two cycles. The subjects of the research consisted of fourth grade teachers and all students of fourth grade totaling 21 students. Data collection techniques used tests, interviews, observations, and documentation. Source triangulation techniques and data collection triangulation techniques used for data validity. Data analysis techniques used interactive analysis techniques with the stages are data reduction, presentation of research data, and drawing conclusions. As results, students' learning activeness increased in five indicators of the pre-action increasing in cycle I, and again increasing in cycle II. The five indicators of learning activeness in this study include paying attention and writing material, asking questions, expressing opinions or ideas, discussing classical problem solving, and presenting learning outcomes. Application of the GNT model can increase student learning outcomes marked by in classical completeness in pre-action by 61.90% increased in cycle 1 to 76.19%, and increased in cycle II to 85.71%. The conclusion of this research is the application of the GNT model can increase the learning activity of fourth grade students of Ngadipurwo Elementary School in social learning.